Educational reform for middle-income trap under digitalization: Culprits, challenges, and strategies in the Philippines - Hara Masatoshi (SocioEconomic Challenges, 2023)
The concept of the middle-income trap (MIT) asserts that economies with middle-income levels often struggle to progress to higher income levels, which is particularly evident in Southeast Asia. Escaping the MIT has been a significant concern, with various factors like governance, infrastructure, and labor markets identified as contributors. Education is a crucial element for developing human capital and driving economic growth. Despite efforts to enhance education, the Philippines has a historical challenge of being stuck in the lower-middle-income trap (LMIT). Limited research on effective education reform strategies to overcome the LMIT in the Philippines is available in government plans and existing studies. The research utilized a mixed method involving both qualitative and quantitative approaches. In the initial qualitative phase, the analysis drew from the Murdoch School's critical political economy and strategic management framework. It revealed that insufficient funding for education, unequal allocation of resources between urban and rural areas, and unfavorable home learning environments are significant factors hindering progress. To address these issues and escape the LMIT, a development strategy was proposed, combining formulation and execution into a unified concept. By tackling problems like misaligned investment priorities, improper resource distribution, lack of mobile infrastructure, and unsupportive learning environments, collaboration among private sectors and universities as cluster networks could drive educational reforms. This, in turn, would lead to societal transformation and economic growth by aligning with societal needs and market demands. Focusing on relevant skills in the digital age is a suitable approach, where skill-oriented education could serve as a cornerstone of the reform efforts.